PENGEMBANGAN MODUL LITERASI IKLIM UNTUK ANAK USIA 10-12 TAHUN DI YAYASAN AS-SYAFIQ JAKARTA UTARA - Elva Susanti Meylani; Rayuna Handawati; Asma Irma Setianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop a climate literacy module for children aged 10-12 inA s-Syafiq Foundation, Warakas District, Jakarta Utara using Research and Development method with ADDIE concept (Analyze, Design, Develop, Implement, and Evaluate). Data collection involved documentation, expert and user questionnaires, as well as pre-test and post-test to assess understanding. The data were analyzed using descriptive statistics. In the Analysis stage, a user profile was developed; the Design stage produced the module syllabus; and the Develop stage resulted in “Aku Sahabat Iklim” module which has been validated by content and media experts with an average score of 4.62 out of 5 (very good). During the Implement stage, small and large trials were conducted to determine implementation strategy for the module. The large-group user trials questionnaire received a score of 3.26 out of 4 (very good), while the test results showed normalized gain score of 45%, suggesting a significant improvement in understanding. In the final stage, Evaluate, module revisions based on the results of experts’ validation and user trials were summarized.